Rheological Characterization of Algerian Crude Oil and Emulsions Water / Oil - Benyerou, D.; Mekkaoui, M.; Hammadi, L.; Boudjenane, N.; Belhadri, M. (Algerian Journal of Research and Technology (AJRT), 2016)
In this paper,a finerheological characterizationwas performed forfive types ofcrude oil from theAlgerianSaharaand severalwater / oilemulsions. This studyallows us to obtain moreknowledge aboutthe rheological behaviorof these samples andprovides us with information ontheirstorageandtransport inpipes.Three qualitiesof water wereused, seawater, drinking water andgroundwater sources. Thetests were carried outat a temperature of23°C usinga sophisticatedrheometerwithcone-plategeometry(the RS600RheoStress from ThermoHaake). The perturbing effectssuch assliding, evaporation, fracturing and diggingwere well controlled. The study shows thatthe rheological behaviorof the fivetypes of crude oilisNewtonian, however, thatemulsionsofvolume concentrationsof30%, 50% and70% ofwaterisnon-Newtonian withtheexistence ofathresholdconstraint. TheBingham, Herschel-BulkleyandostwaldDe Waele modelswere used andadjustedso to correctly representthe rheological behaviorof these materials.